1986
DOI: 10.1073/pnas.83.13.4650
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence and expression of the selenocysteine-containing polypeptide of formate dehydrogenase (formate-hydrogen-lyase-linked) from Escherichia coli.

Abstract: The gene (fdhF) coding for the selenopolypeptide of the benzylviologen-linked formate dehydrogenase of Escherichia coli was cloned and its nucleotide sequence was determined. ThefdhF gene contains, within an open reading frame coding for a protein of 715 amino acids (calculated molecular weight, 79,087), an opal (UGA) nonsense codon in amino acid position 140. Existence of this nonsense codon was confirmed by physical recloning and resequencing. Internal and terminal deletion clones and lacZ fusions of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
223
0
6

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 446 publications
(231 citation statements)
references
References 19 publications
2
223
0
6
Order By: Relevance
“…Within the same year Zinoni et al (1986) established that TGA also encoded the selenocysteine discovered in bacterial formate dehydrogenase by Jones et al (1979). Starting from these observations, the complex biosynthesis of selenoproteins was unraveled for bacteria in a transatlantic cooperation that remains inseparably associated with the names of Stadtman and Böck (Zinoni et al, 1986;Böck and Stadtman, 1988;Böck et al, 1991a,b). The attempts to understand eukaryotic selenoprotein biosynthesis has revealed homologies but also marked differences (Berry et al, 1991(Berry et al, , 1993, and has not yet yielded a satisfying comprehensive view.…”
Section: Introduction: Some Historical Landmarksmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the same year Zinoni et al (1986) established that TGA also encoded the selenocysteine discovered in bacterial formate dehydrogenase by Jones et al (1979). Starting from these observations, the complex biosynthesis of selenoproteins was unraveled for bacteria in a transatlantic cooperation that remains inseparably associated with the names of Stadtman and Böck (Zinoni et al, 1986;Böck and Stadtman, 1988;Böck et al, 1991a,b). The attempts to understand eukaryotic selenoprotein biosynthesis has revealed homologies but also marked differences (Berry et al, 1991(Berry et al, , 1993, and has not yet yielded a satisfying comprehensive view.…”
Section: Introduction: Some Historical Landmarksmentioning
confidence: 99%
“…Related studies were mainly conducted with formate dehydrogenase in E. coli, which also contains selenium as a selenocysteine residue integrated in the peptide chain. The insertion of the selenocysteine is encoded by the triplet TGA, which usually functions as a stop codon (Zinoni et al, 1986;Böck and Stadtman, 1988;Böck et al, 1991a). Recoding of TGA as a selenocysteine codon requires an mRNA secondary structure called SECIS (for selenocysteine-insertion sequence), which, in bacteria, is localized immediately downstream of the UGA codon.…”
Section: The Biosynthesis Of Selenoproteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzyme is a homotetramer of -22 kd subunits and it is located in the cytosol. The genes for mouse GPXI and Escherichia coli formate dehydrogenase H were the first selenoprotein genes to be sequenced, which revealed that Sec is encoded by TGA [18,103]. Bovine erythrocyte GPX1 has been crystallized and its three-dimensional structure determined [29].…”
Section: The Glutathione Peroxidase Familymentioning
confidence: 99%
“…Thus, Sec is the 21st genetically encoded amino acid translated into proteins by reading of the UGA codon (194). GPx 1 was the first mammalian gene shown to contain UGA in its open reading frame, which corresponded to the site of Sec in the protein sequence (60,356). Shortly after, it was indeed demonstrated that Sec is incorporated into protein by a tRNA molecule with an anti-codon complementary to UGA (200).…”
Section: From Uga To Selenoproteinsmentioning
confidence: 99%